2020
DOI: 10.22364/laize
|View full text |Cite
|
Sign up to set email alerts
|

Latvijas augsti izglītotie emigranti: izglītības un darba pieredze Latvijā un ārvalstīs

Abstract: Monogrāfijā augsti izglītoto emigrantu problēmas tiek skatītas mikro, mezo un makro līmenī. Tas ļauj pievērst uzmanību gan indivīdu izvēlēm, gan ģimenes un radinieku, gan sociālo tīklu un organizāciju ietekmei, gan arī ekonomiskiem un politiskiem faktoriem. Atbilstoši šiem līmeņiem veidots pētījuma teorētiskais pamats un Eiropas Savienības dalībvalstu un citu valstu emigrācijas pētījumu konteksts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 108 publications
(183 reference statements)
0
1
0
Order By: Relevance
“…Notwithstanding the theoretical sophistication of Laitin's reasoning, subsequent studies have shown that a majority of Russian speakers in Estonia, Latvia, and Lithuania have a preference for integration over assimilation (Kemppainen et al 2004;Kronenfeld 2005;Pisarenko 2006;Šūpule 2007;Kasatkina 2006). These studies show clear evidence that Russian speakers commonly have a desire to learn the culture and language associated with their state of residence, whilst simultaneously maintaining Russian cultural and linguistic identities.…”
Section: Russian Speakers and Integrationmentioning
confidence: 99%
“…Notwithstanding the theoretical sophistication of Laitin's reasoning, subsequent studies have shown that a majority of Russian speakers in Estonia, Latvia, and Lithuania have a preference for integration over assimilation (Kemppainen et al 2004;Kronenfeld 2005;Pisarenko 2006;Šūpule 2007;Kasatkina 2006). These studies show clear evidence that Russian speakers commonly have a desire to learn the culture and language associated with their state of residence, whilst simultaneously maintaining Russian cultural and linguistic identities.…”
Section: Russian Speakers and Integrationmentioning
confidence: 99%